Discovery of 5-substituent-N-arylbenzamide derivatives as potent, selective and orally bioavailable LRRK2 inhibitors. Issue 17 (1st September 2017) - Ding, Xiao; Dai, Xuedong; Long, Kai; Peng, Cheng; Andreotti, Daniele; Bamborough, Paul; Eatherton, Andrew J.; Edge, Colin; Jandu, Karamjit S.; Nichols, Paula L.; Philps, Oliver J.; Stasi, Luigi Piero; et al.
Graphical abstract: Abstract: Leucine-rich repeat kinase 2 (LRRK2) has been suggested as a potential therapeutic target for Parkinson's disease. Herein we report the discovery of 5-substituent- N -arylbenzamide derivatives as novel LRRK2 inhibitors. Extensive SAR study led to the discovery of compounds8e, which demonstrated potent LRRK2 inhibition activity, high selectivity across the kinome, good brain exposure, and high oral bioavailability.